Las competencias TIC y la lectura digital en los estudiantes de 5to de secundaria de la IEP genes 2022 - García Aguirre, Pablo Jesús (2024)
The objective of this research is to determine if there is a relationship between ICT skills and digital reading in 5th grade students. secondary school in the IEP GENES. This study has a quantitative approach, basic type, ordinal level and with a non-experimental descriptive correlational, cross-sectional design in the 7 GENES educational units is 293 and the probabilistic sample of 50 students that was taken from the IEP GENES II.             Two instruments were applied, a reading survey and a questionnaire with the application of a Likert Scale validated by expert judgment, the results were processed using the statistical software SPSS version 27. The results obtained were: 76.7% had a low level in With the use of ICT, 53.3% of students reached a level of reading comprehension at Home. In this study, with a significance level of 5%, it is concluded that there is a moderate direct compensation between the use of ICTs and digital reading comprehension (Rho =0.459, P<0.05), which demonstrates that there is a moderate relationship between the use of ICTs and digital reading comprehension. ICT and digital reading comprehension in 5th grade secondary school students, when obtaining the statistics regarding the degree of tension between the variables determined by Spearman's Rho, interpreting that there is a moderate positive relationship between the specific variables, compared to the (grade of statistical significance) p < 0.05.